DIALOG IMAJINER DENGAN HANS KELSEN TENTANG "KEADILAN" - Kusumohamidjojo, Budiono (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2005)
This articlewas written in 1987 and was not published to date. It deals withKelsen's concept of justice that is based on his theory of pure law. Kelsen's work was written in the speculative tradition of the European Staatsrecht, which does not necessarily resemble constitutional law in the English analytical tradition. The positive law that governs the daily life should be the result of legal studies that in turn has to be liberated from political interests. For that sake man has to revert to the Grundnorm, by means of continuous application of teleology (which is commensurate with the term "hermeneutics" in modern philosophy). Kelsen was concerned about the trend of formalism as a short cut in the pursuit of justice, which could fire back on the coherence of the social process.